PHILOSOPHY OF INTEGRATED NATURAL SCIENCE LEARNING - Anggit Grahito Wicaksono; Ifa Hanifa Rahman (Program Studi Pendidikan IPA, Fakultas Ilmu Pendidikan, Universitas Trunojoyo Madura, 2022)
Philosophically, natural sciences as a building of knowledge can study ontology (what you want to know), epistemology (how to acquire knowledge), and axiology (what is the value of knowledge). Natural Science as a building of science has properties that are closely related to natural objects. The problems that occur with natural objects are holistic. This holistic problem requires problem-solving from various disciplines, especially in the natural sciences. Based on the scope of the research above, this article aims to investigate integrated natural science learning in a philosophical review (ontology, epistemology, axiology). The qualitative method is applied in this study. Studies conducted to solve problems based on a critical and in-depth analysis of pertinent library materials are known as library research. Overviews of ontology, epistemology, and axiology state that integrated natural science learning, students are expected to be able to relate to other disciplines such as physics, astronomy, chemistry, geology, biology, technology, environment, and health and safety. This type of instruction uses natural science to present natural phenomena and events holistically and to develop students' problem-solving skills. The recommendation given is that teachers should tend to the interdisciplinary study of the natural sciences.